(untitled) (Cadernos de Sociomuseologia, 2019)
This volume of Sociomuseoly Journal presents the minutes of the ICAMT Worshop, held in our department in early 2018. We present a set of communications dealing with different subjects marked by different conceptual approaches. This joint event underscores the interest our department has shown over the years, to promote a dialogue with international committees and affiliated organizations of ICOM. This dialogue has already been held twice with the ICTOP, recently with CECA, and several times with MINOM. These joint events, always allowed an open debate on different views about Museology, which leave always enriched the students, teachers and researchers. In other contexts we dialog with the ICR, and more recently we approach the ICOFOM. I am sure, that once again, this dialogue was possible and that ties of friendship and professional commitments were created. In times of uncertainty, where intolerance grows every day, this joint work gives meaning to the Museology that is attentive to Human Rights Mário Moutinho